Telehealth-facilitated palliative care enables more people to die at home: An analysis of clinical outcomes and service activity data - Helen M. Haydon; Mojtaba Lotfaliany; Andrew Broadbent; Centaine L. Snoswell; Anthony C Smith; Julie-Ann Brydon; Liam J. Caffery; Emma E. Thomas (BMC Palliative Care)
Abstract Background Telehealth-facilitated models of palliative care are a patient-focused way to deliver specialist care in or closer to home for people with a life-limiting illness. Telehealth can increase access to palliative care and support people experiencing symptoms of advanced disease in their own home, reducing the discomfort of travel. This retrospective cohort study examines the activity and outcomes of a regional telehealth-facilitated palliative care service to (i) describe which patients are most likely to use telehealth; and (ii) explore possible impacts of telehealth on patient outcomes including place of death, timely access to care, responsiveness to urgent needs and pain management. Methods Analysis of service activity data (patient demographics, care modality, consultation frequency) and Palliative Care Outcomes Collaborative data registry (place of death, timely access to palliative care, responsiveness to urgent needs as measured by time in unstable phase, pain management) were undertaken. Outcomes were compared between patients who had no videoconsultations (n = 683) and those who had one or more videoconsultations (n = 524). Results Compared to people who had no videoconsultations, those who had at least one appointment via video were: more than twice as likely to die at home and spent a shorter amount of time in the unstable phase of palliation. Mixed results were found regarding timely access to palliative care. There was no significant difference in pain management between consultation modes. Conclusion Telehealth-facilitated palliative care has multiple benefits, including the increased likelihood of fulfilling someone’s wish to die at home, often their preferred place of death.